Interactions of Alginate-Deferoxamine Conjugates With Blood Components and Their Antioxidation in the Hemoglobin Oxidation Model - Sun, Tong; Guo, Xi; Zhong, Rui; Wang, Chengwei; Liu, Hao; Li, Hao; Ma, Lu; Guan, Junwen; You, Chao; Tian, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
While deferoxamine (DFO) has long been used as an FDA-approved iron chelator, its proangiogenesis ability attracts increasing number of research interests. To address its drawbacks such as short plasma half-life and toxicity, polymeric conjugated strategy has been proposed and shown superiority. Owing to intravenous injection and application in blood-related conditions, however, the blood interactions and antioxidation of the DFO-conjugates and the mechanisms underlying these outcomes remain to be elucidated. In this regard, incubating with three different molecular-weight (MW) alginate-DFO conjugates (ADs) red blood cells (RBCs), coagulation system, complement and platelet were investigated. To prove the antioxidant activity of ADs, we used hemoglobin oxidation model in vitro. ADs did not cause RBCs hemolysis while reversible aggregation and normal deformability ability were observed. However, the coagulation time, particularly APTT and TT, were significantly prolonged in a dose-dependent manner, and fibrinogen was dramatically decreased, suggesting ADs could dominantly inhibit the intrinsic pathways in the process of coagulation. The dose-dependent anticoagulation might be related with the functional groups along the alginate chains. The complements, C3a and C5a, were activated by ADs in a dose-dependent manner through alternative pathway. For platelet, ADs slightly suppressed the activation and aggregation at low concentration. Based on above results, the cross-talking among coagulation, complement and platelet induced by ADs was proposed. The antioxidation of ADs through iron chelation was proved and the antioxidant activity was shown in a MW-dependent manner.